The Correlation Among Students Emotional Intelligence and reading motivation on reading comprehension achievement of eleventh grade students of SMA N 2 Kota Lubuk Linggau - Herawati, Herawati (Lentera: Jurnal Ilmiah Kependidikan, 2017)
Theory of emotional intelligence has been proven to contribute to the teaching and learning process, and increase studentsâ achievement. This research was aimed at investigating if there was any correlation among emotional intelligence, reading motivation on reading comprehension achievement of eleventh grade students of SMAN 2 Kota Lubuklinggau. Two hundred and ninety four students participated in this research. Emotional intelligence questionnaire, reading motivation questionnaire and studentsâ reading comprehension test were used as the instruments. Analyses by Pearson Product-Moment Correlation revealed that there was correlation between emotional intelligence and reading comprehension achievement with r-obtained (.155) and p (.008). At the same time, there was also correlation between reading motivation and reading comprehension achievement with robtained (.165) and p (.005). Furthermore, regression analyses showed that emotional intelligence and reading motivation could predict reading comprehension by explaining 4.6% of the changes in reading comprehension achievement respectively.